SHORELINE SENSITIVITY INDEX TO OIL SPILLS IN NUSA PENIDA MARINE PROTECTED AREA (MPA), BALI - Putra, IPG Eka Handrayana; Osawa, Takahiro; Astawa Karang, I Wayan Gede (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2021)
The Shoreline Sensitivity Index(SSI) is one crucial aspect to know in protecting the coast from all threats, including oil spills. This study aims to determine the shoreline's sensitivity for oil spills based on several oceanographic parameters: shoreline type, tidal range, slope, and wave high in Nusa Penida, Map Protection Area (MPA). The weight overlay method was employed to apply the geographic information system (GIS). Each parameter component was scored as five categories before the weighted overlay. The shoreline sensitivity level of Nusa Penida island is divided into five categories: very low sensitive, low sensitive, medium sensitive, high sensitive, and very high sensitive. As the results, the SSI was categorized during the east monsoons (from June to August) and during the west monsoons (from December to February) is at a low sensitivity level to very high sensitivity. SSI during east monsoons there is about 60.05% (627.33 ha) in the medium, 9.39% (98.11 ha) in the high, and 2.39% (24.99 ha) in the very high sensitive. The SSI during the west season is about 78.16% (816.95 ha) with the medium, 19.43% (203.11 ha) with the high, and 2.39% (24.99 ha) with the very high sensitive. The difference in wave height during east and west monsoons greatly affects the sensitivity level of the Nusa Penida coastal area. However, sensitivity level in Jungutbatu and Lembongan Villages are not affected by the east or west monsoons. Keywords: Shoreline Sensitivity; GIS; Nusa Penida; Oil Spill.